Religious Educational Messages In Despacito Lyrics by Gen Halilintar (Semiotic Analysis) - Imam Bahroni; Hilda Waslatul Hidayah (At-Ta'dib, 2018)
Spreading religious educational message was Islamic mission to overspread the kindness in this modern era. In the modern era the communication of technology and information would be owned by everyone. We are as muslim, we can put the islamic values in the communication technology and information. And one of medium did the people like is the music, because the music has the fervency and harmony. it could make influenced the listeners by emotional through the lyric. One of the popular music in this era is “Despacito”. Originally, this Spanish song has the uneducation purpose, and Gen Halilintar had changed the lyric by Islamic values be source of Al-Qur’an and Hadits. The purpose of this research is to know the religious educational message and to know the Islamic values in Despacito lyric by Gen Halilintar. The analysis method that used in this research was semiotic analysis by Roland Barthes, because the researcher used more text and the analysed by the sign and signed with connotation and denotation form by sourcing Al-Qur’an and Hadits. The output from this process of writing is we get three main of Religious Educational Message there are The faith, Islamic law and the morals.